2020
DOI: 10.1186/s40816-020-00214-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological activities of methanol extract of Artemisia vulgaris L. leaves

Abstract: Background Artemisia vulgaris commonly known as “mugwort” is a very important medicinal plant which is used widely for the treatment of various ailments traditionally. The present studies aimed to conduct preliminary phytochemical screening and evaluate antioxidants and analgesic activities of leaves extract. Results Phytochemical screening showed the presence of saponins, glycosides, flavanoids, protein, triterpenoids in leaves extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Table 4 lists the many chemical constituent structures of the plant [27,38,40,41]. The aerial parts contain carbohydrates (40%), amino acids, phenolic compounds (9.8%), protein (2.9%), triterpenoids, steroids, glycosides, saponins and flavonoids [42,43]. Twenty known flavonoids, namely apigenin, eriodictyol, chrysoberyl, eupafolin, eriodictyol, homoeriodictyol, isorhamnetin, jaceosidin, diosmetin, luteolin, luteolin 7-glucoside, kaempferol 3-glucoside, kaempferol 7-glucoside, kaempferol 3-rhamnoside, kaempferol 3-rutinoside, quercetrin, quercetin 3-glucoside, quercetin 3-galactoside, rutin, tacrine and vitexin, are observed [3].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 lists the many chemical constituent structures of the plant [27,38,40,41]. The aerial parts contain carbohydrates (40%), amino acids, phenolic compounds (9.8%), protein (2.9%), triterpenoids, steroids, glycosides, saponins and flavonoids [42,43]. Twenty known flavonoids, namely apigenin, eriodictyol, chrysoberyl, eupafolin, eriodictyol, homoeriodictyol, isorhamnetin, jaceosidin, diosmetin, luteolin, luteolin 7-glucoside, kaempferol 3-glucoside, kaempferol 7-glucoside, kaempferol 3-rhamnoside, kaempferol 3-rutinoside, quercetrin, quercetin 3-glucoside, quercetin 3-galactoside, rutin, tacrine and vitexin, are observed [3].…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…The main components are artinnium b, artemisia ketone, D-fructose, 1, 8-cenol, D-limonene, yomogin, 1, 2, 3, 4-diepoxy-11(13)eudesmen-12, 8-olide camphor, piperitone, present in the plant [48]. The flavonoids isoquercetrin, hydroxycinnamic acids, kaempferol, gentisic, caffeic, p-coumaric, camphor (11.89%), ferulic acids b-thujone (19.19%), borneol (4.44%), chrysanthenone (4.48%), sabinene (11.29%) and germacrene D (8.42%) and several quinic acid derivatives chlorogenic, 3-caffeoylquinic, 1,5-dicaffeoylquinic, 1,3-dicaffeoylquinic, 3,4-dicaffeoylquinic, 3,5-dicaffeoylquinic, 1,4-dicaffeoylquinic and 4,5-dicaffeoylquinic acids, 5-feruloyl, quinic and other phenolic compounds are present in the plant [27,35,43]. α-Thujone, caryophyllene oxide, 1, 8 cineole are the major vital oil [49].…”
Section: Sno Part Used Constituentmentioning
confidence: 99%
“…If combined with the optimal drug-to-solvent ratio and with three cycles of extraction to let total exhaustion of the matrix, it is also possible to lower significantly the amount of organic solvent that in our study was found to be optimal in a ratio 1 : 2 v/v in combination with water, which is a percentage significantly lower compared to that of many studies where the extractant is represented by at least 50 % v/v of organic solvent. [29,30] The analysis of the phytochemical composition of cowpea leaves displayed that most of the compounds occurring within the matrix are conjugated with glycosides or sugar moieties that are likely to increase the overall polarity of the phytocomplex. This may justify the need for a low amount of ethanol to obtain the optimal recovery of antioxidant compounds, making cowpea leaves an interesting matrix as regards their usage as a food supplement.…”
Section: Optimized Extraction Protocol and Phytochemical Characteriza...mentioning
confidence: 99%
“…The extracted essential oil (EO) of Curcuma angustifolia Roxb. was analyzed for phytochemicals screening using the standard techniques with a slight modification (Thangjam et al 2020;Iqbal et al 2015).…”
Section: Phytochemical Screeningmentioning
confidence: 99%